How Belonging to a Minority Group, Receiving a Hiring Decision and Getting Feedback on Test Results Affect the Intention to File a Complaint: The Mediating Role of Perceived Discrimination in Hiring - Denis, Pascale; Cossette, Michel; Stamate, Alina; Haeck-Pelletier, Justine; Sauvé, Geneviève (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2024)
AbstractObjective indicators, such as minority hiring rates or number of complaints, often fail to fully represent actual discrimination in hiring processes, particularly against racial and ethnic minorities (McGonagle et al., 2016). Despite legal efforts in Quebec to increase employment of minorities, their ongoing underrepresentation points to the need to examine discrimination in terms of perceived experiences. In line with Anderson (2011), we investigated perceived discrimination in hiring (PDH), its predictors and its effect on the intention to file a discrimination complaint, rather than solely considering actual complaints. Using a quasi-experimental design, we simulated a fictitious hiring process with 361 students from French-speaking Canadian universities. First, we confirmed the three dimensions of the recently developed PDH scale: differential treatment; breach of psychological contract; and non-competency-based assessment (Haeck-Pelletier, 2022). Second, using structural equation modelling (SEM), we found mediation effects: PDH scores were higher across all dimensions when a candidate belonged to a minority group, received a negative hiring decision or did not receive feedback on test results. However, only differential treatment predicted a candidate’s intention to file a complaint. In addition to this first empirical test of Anderson’s model, the results suggest that organizations should address perceptions of unfair treatment due to minority group membership by identifying and modifying the practices that contribute to them. The eventual outcome would be a more representative workforce.